Material properties of high–strength beryllium–free copper alloys. (1st January 2015) - Altenberger, Igor; Kuhn, Hans–Achim; Müller, Hilmar R.; Mhaede, Mansour; Gholami–Kermanshahi, Mozghan; Wagner, Lothar
High strength copper alloys can be produced either by generating very fine grained low alloyed single phased or precipitation hardened copper alloys or by highly alloyed precipitation hardened copper alloys. The latter process requires special processing methods such as spray forming in order to achieve a sufficiently homogeneous microstructure. Systematic investigations on the aging behaviour of the highly alloyed nickel–manganese bronze CuNi20Mn20 demonstrate that fully crystalline copper alloys with hardness exceeding 500 HV can be produced. In addition to age hardening, swaging or severe plastic surface deformation can be used for additional grain refinement and strain hardening before precipitation hardening. In contrast to CuMn20Ni20, the low–alloyed precipitation hardened copper alloy CuNi3Si1Mg exhibits excellent thermal and electrical conductivity while maintaining acceptable strength after swaging and precipitation hardening. Finally, a systematic comparison between spray–formed or precipitation high strength hardened copper alloys and classical well–known materials such as steels or aluminium alloys was carried out by using material property charts (Ashby–maps) and highlighting the fields of application and unique property combinations of copper alloys.